Characterization of human umbilical cord mesenchymal stem cells following tissue mass culture - Yang, L. M.; Liu, Y.; Zhao, J.; Hao, L. M.; Huang, K. X.; Jiang, W. H. (Cellular and Molecular Biology, 2014)
The human umbilical cord represents a promising resource of mesenchymal stem cells (MSCs). In order to improve our understanding of MSCs derived from human umbilical cord (UC-MSCs), we isolated UC-MSCs from human umbilical cord tissues through a direct culture approach. We performed a comprehensive characterization of these cells based on analyses of morphology, growth features, cell surface antigen markers and differentiation capacity. All these analyses validated their stem cell nature. The UC-MSCs presented a spindle-shaped morphology and could be subcultured for up to 15 passages without losing their cellular features. Moreover, these UC-SMCs presented an expression profile of cell surface antigens similar to other MSCs: positive for CD44, CD90, and CD105 expression and negative for CD34, CD31, and CD45 expression. Differentiation assays further validated the multipotency of UC-MSCs by inducing these cells into osteoblasts, adipocytes and functional hepatocytes. Our studies clearly demonstrated that UC-MSCs resemble other types of MSCs in many aspects and have a great potential to be applied in tissue engineering and regenerative medicine.